If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(x) = (radx + -2) + -3 Multiply F * x xF = (radx + -2) + -3 Reorder the terms: xF = (-2 + adrx) + -3 Remove parenthesis around (-2 + adrx) xF = -2 + adrx + -3 Reorder the terms: xF = -2 + -3 + adrx Combine like terms: -2 + -3 = -5 xF = -5 + adrx Solving xF = -5 + adrx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1adrx' to each side of the equation. -1adrx + xF = -5 + adrx + -1adrx Combine like terms: adrx + -1adrx = 0 -1adrx + xF = -5 + 0 -1adrx + xF = -5 Reorder the terms: 5 + -1adrx + xF = -5 + 5 Combine like terms: -5 + 5 = 0 5 + -1adrx + xF = 0 The solution to this equation could not be determined.
| ln(3-7x)=-2 | | 3x+1.66=1.8 | | 10x^3+58x^2+43x-11=0 | | 10x^3+58x^2+43x-11=f(x) | | 24x=-16x^2+6 | | 5x-7y=29 | | 5cos(x)=0 | | 0.04*0.8= | | x+(2x+15)=150 | | 0.75d-0.67d=0.67+6 | | 88+5x= | | K-(-6)=-33 | | x+0.5x+0.25x+1=100 | | x+(2x-15)=150 | | x+0.5x+0.75x+1=100 | | 6x-2=64(2x) | | 5+2+x=9 | | 4x=12-x | | sin*2*t= | | 3y+3=6(y+1) | | (2x+5)+(2x+2)=4(x-1)+9 | | (5-2x)(2x+1)=4x^2-25 | | (y+1)(y-2)= | | 3m/7=9 | | (5-2x)(2x+7)=4x^2-25 | | (6x+4)-(-6x+5)= | | Y(5-2)=52 | | (x+12)*4=90-2x | | 4x^4-2x^3+7x^2+3x+9=0 | | 2r-.75=1 | | (2x+1)+(-1x+9)= | | 4(x+12)=90-2x |